GlobaLID: A new database and interactive web tool for provenancing archaeological metals - Thomas Rose; Sabine Klein; Yiu-Kang Hsu; Katrin J. Westner (Archeomatica, 2022)
Lead isotope signatures of non-ferrous metals are a well-established approach to tracing ore sources, which can provide important information to reconstruct past exchange networks. Like many other provenancing methods, the usefulness of lead isotopes in provenance studies relies heavily on a comprehensive reference database. GlobaLID aims to provide an infrastructure for a central storage of lead isotope data. It consists of a comprehensively evaluated database with extensive geological and contextual information and of a web application that provides an intuitive interface to interact with the database, options for comparison with own sample data, and to design and download publication-ready lead isotope plots.